Investigation of the relationship between Ironworker's gait stability and different types of load carrying using wearable sensors. (January 2022) - Yoon, Jihwan; Lee, Bogyeong; Chun, Jaeyoul; Son, Bosik; Kim, Hyunsoo
Highlights: Data is collected based on the gait of the ironworker using IMU sensor. Gait stability of each ironworker is quantified using DTW algorithm. Effects of various loads carried on ironworker's gait stability were investigated. Ironworker gait stability is affected by load carrying weight and handling method. Abstract: Load carrying can cause changes in gait stability. Maintaining gait stability (body balance) on a steel frame is an important factor in the prevention of accidents. However, the effects of load carrying on a restricted surface (width), where ironworkers usually perform their jobs, have rarely been investigated. In this context, this study investigates the effect of different types of load-carrying scenarios on the gait stability of ironworkers. Accordingly, to identify the relationships between the weight of load, type of load-carrying method, type of load-carrying tools, and gait stability, represented as the dynamic time warping (DTW) values, an experiment was conducted under 15 different load-carrying conditions. The change in DTW according to the different load conditions was as follows: For one-handed load-carrying using a toolbox, the average DTW values were 23.31 at a weight of 3 kg, 23.80 at 6 kg, 33.20 at 10 kg, 65.84 at 16 kg, and 103.50 at 20 kg. Moreover, for one-handed load-carrying using a bucket, the average DTW values were 23.07 at 3 kg, 24.76 at 6 kg, 34.35 at 10 kg, 77.52 at 16 kg, and 108.28 at 20 kg. Finally, in the case of both-handed load carrying, the average DTW values were 24.31 at 6 kg, 28.11 at 10 kg, 27.23 at 16 kg, 37.90 at 20 kg, and 40.96 at 32 kg. As the weight of the load increased, the DTW values in almost all the experimental cases also increased. Furthermore, the DTW values for bucket carrying and tool box carrying showed clear differences above a certain weight (16 kg). Thus, the results of the experiments indicate that different types of load-carrying conditions significantly affect the ironworkers' gait stability as they walk on a steel frame. Finally, the calculated DTW values were compared with the subjective perceived ratings to validate the experimental results. The DTW value was highly correlated with the subjective perceived rating scores (Pearson coefficient: 0.929). The results of this study will facilitate the use of gait stability measurements to enhance the construction safety of ironworkers.